Endothelial Cell Response to Narrow Diameter Nylon Tubes Exhibiting Internal Nanotopography - Berry, C.; McCloy, D.; Affrossman, S. (Current Nanoscience, 2008)
The use of three dimensional scaffolds in tissue engineering is well reported, as is the exploitation of nanotopography to influence cell response. To date, due to fabrication limitations, the combination of these two has experienced limited research. This paper reports on the use of polymer demixing, a rapid and cheap nanofabrication method, to create a defined nanotopography in 0.5mm diameter nylon tubes. Results indicate that the resultant nano-island topography reduced endothelial cell adhesion and spreading, strongly influenced cell morphology, and appeared to increase endocytic activity. The use of such constructs that boast topographical cues have great potential in tissue and cell engineering studies for future clinical use, in particular with respect to conduits and stents.